Teknik Penilaian Produk Materi PAI Terpadu Untuk MI/SD - Solekan Solekan; Halili Halili (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2021)
One of the most prominent implications of the implementation of the 2013 curriculum primarily for the SD / MI level is the use of integrated thematic learning. PAI subject matter in MI / SD must refer to core competencies where basic competencies are classified into four competency aspects (spiritual, social, knowledge and skills attitudes). That is, the material of PAI MI in the MI 2013 curriculum is expanded, by implementing integrated thematic learning implementation steps which include three main components, namely preliminary activities, core activities, and closing activities. The purpose of this study is to provide an analysis of the meaning, function, purpose and use of the stages of implementation of Integrated Islamic Education Material Development for MI / SD and the implementation of the steps for implementing Integrated Islamic Education Material Product learning for MI / SD which includes three main components. In this study the authors used data collection methods with documentation methods, as in the data collection techniques in library research (library research). The documentation method is a method used by researchers to objects or documents such as magazines, books, journals, meeting minutes and so on. The object of study in this article is focused on understanding the meaning, function, purpose, and use of the stages of implementing the development of integrated Islamic education materials for MI / SD and the implementation of the steps for implementing Integrated PAI material product learning for MI / SD which includes three main components.